2011
DOI: 10.1007/s10549-011-1348-y
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic receptors (β-AR) regulate VEGF and IL-6 production by divergent pathways in high β-AR-expressing breast cancer cell lines

Abstract: Activation of β-adrenergic receptors (β-AR) drives proangiogenic factor production in several types of cancers. To examine β-AR regulation of breast cancer pathogenesis, β-AR density, signaling capacity, and functional responses to β-AR stimulation were studied in four human breast adenocarcinoma cell lines. β-AR density ranged from very low in MCF7 and MB-361 to very high in MB-231 and in a brain-seeking variant of MB-231, MB-231BR. Consistent with β-AR density, β-AR activation elevated cAMP in MCF7 and MB-36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 24 publications
7
118
0
2
Order By: Relevance
“…Results from several recent studies have indicated that stress-induced catecholamines upregulate the synthesis of many proangiogenic factors, such as VEGF, through the b2-AR-mediated signaling pathway in a variety of malignant tumor cells and induce angiogenesis in the tumor tissues (Thaker et al 2006, Madden et al 2011, Park et al 2011. It has also been shown that norepinephrine stimulates the production of MMP2 and MMP9, which mediate extracellular matrix degradation and tissue remodeling and induce angiogenesis, through the b2-AR signaling pathway in tumor cells and tumor-associated macrophages (Cole & Sood 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Results from several recent studies have indicated that stress-induced catecholamines upregulate the synthesis of many proangiogenic factors, such as VEGF, through the b2-AR-mediated signaling pathway in a variety of malignant tumor cells and induce angiogenesis in the tumor tissues (Thaker et al 2006, Madden et al 2011, Park et al 2011. It has also been shown that norepinephrine stimulates the production of MMP2 and MMP9, which mediate extracellular matrix degradation and tissue remodeling and induce angiogenesis, through the b2-AR signaling pathway in tumor cells and tumor-associated macrophages (Cole & Sood 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are three β-AR subtypes, β 1 -AR, β 2 -AR and β 3 -AR, each with specific physiological actions. The expression of β-ARs has been characterized in several breast cancer cell lines [Vandewalle et al 1990;Badino et al 1996;Slotkin et al 2000;Sloan et al 2010;Madden et al 2011;Park et al 2011;Shi et al 2011] as well as in collections of human breast cancer tissue samples [Draoui et al 1991;Powe et al 2011;Shi et al 2011] and in mammary tumours from rodents induced by administration of dimethylbenz(a)anthracene [Marchetti et al 1991] (see Table 1). Studies have shown that these β-ARs are predominantly of the β 2 -adrenergic receptor (β 2 -AR) subtype [Draoui et al 1991;Badino et al 1996;Slotkin et al 2000] and are functionally active, with pharmacological ligation resulting in significant cAMP production [Vandewalle et al 1990;Badino et al 1996;Slotkin et al 2000;Sloan et al 2010;Madden et al 2011].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In preclinical studies, researchers had observed the expression of beta-adrenergic receptors in a few breast cancer cell lines and human breast cancer tissue samples (Madden et al, 2011;Park et al, 2011;Powe et al, 2011). Beta-adrenergic receptor signaling had been demonstrated to accelerate angiogenesis through increasing the expression of vascular endothelial growth factor (VEGF) (Lutgendorf et al, 2003;Thaker et al, 2006;Yang et al, 2006;Zhang et al, 2010) and interleukin-6 (IL-6) (Thaker et al, 2006;Sloan et al, 2010), promote breast cancer growth (Cakir et al, 2002;Thaker et al, 2006;Shi et al, 2011), recurrence and metastasis (Benish et al, 2008;Avraham et al, 2010;Sloan et al, 2010) and reduce apoptosis of cancer cells (Sastry et al, 2007;Zhang et al, 2009;Sood et al, 2010;Set al, 2011).…”
Section: Introductionmentioning
confidence: 99%